Alternative plant habitats for common phytoseiid predators of the cassava green mite (Acari: Phytoseiidae, Tetranychidae) in northeast Brazil - de Moraes, G.J.; de Alencar, J.A.; de Lima, J.L.S.; Yaninek, J.S.; Delalibera Jr, I. (1993)
A survey was conducted to identify possible alternative plant habitats of the most common phytoseiid predators associated with the cassava green mite, Mononychellus tanajoa (Bondar), in their native environment in northeast Brazil. Thirty-two phytoseiid species were collected, including Amblyseius aripo (DeLeon), Amblyseius idaeus (Denmark and Muma) and Amblyseius limonicus Garman and McGregor s.l., the three predators previously shown as the most common on cassava. In increasing order, A. idaeus, Phytoseius guianensis DeLeon and A. aripo were the most common phytoseiids collected on the plant habitats examined. A. limonicus s.l. was one of the least common phytoseiids on plants other than cassava. Altermative plant habitats seem important in harboring A. aripo and A. idaeus, but not A. limonicus s.l..